Pharmacological targeting of IRE1 in cancer - Pelizzari Raymundo, D; Doultsinos, D; Guillory, X; Carlesso, A; Eriksson, LA; Chevet, E (Cell Press, 2020)
IRE1α (inositol requiring enzyme 1 alpha) is one of the main transducers of the unfolded protein response (UPR). IRE1α plays instrumental protumoral roles in several cancers, and high IRE1α activity has been associated with poorer prognoses. In this context, IRE1α has been identified as a potentially relevant therapeutic target. Pharmacological inhibition of IRE1α activity can be achieved by targeting either the kinase domain or the RNase domain. Herein, the recent advances in IRE1α pharmacological targeting is summarized. We describe the identification and optimization of IRE1α inhibitors as well as their mode of action and limitations as anticancer drugs. The potential pitfalls and challenges that could be faced in the clinic, and the opportunities that IRE1α modulating strategies may present are discussed.